Peran Perempuan dalam Proses Bina Damai: Studi Kasus Aktivis Perempuan di Sudan Selatan (2005-2018) - Maria Fryna Angelica Andris; Edwin Martua Bangun Tambunan (Parahyangan Center for International Studies, 2023)
Amidst the oppressive patriarchal culture, the lingering conflict in South Sudan between 2005-2018 has caused women to experience discrimination and violence. The dissatisfaction of women activists with the social system and the protracted conflict eventually encouraged them to participate in the peacebuilding process. This article examines the role of women in the peacebuilding activities by describing the work of women activists in South Sudan. The study is conducted qualitatively by applying the case study method and utilizing the Feminist methodology to comprehensively examine individuals and women's activist organizations activities in peacebuilding through the women perspective. This research finds that women activists play a role in the peacebuilding process at every level of the actor pyramid, from grassroots, middle, to top level. Positive and transformative changes take place as the result of their roles. At the top level, the peacebuilding efforts have encouraged the South Sudanese government to involve women activists in the peace negotiation process withSudan and ensure gender equality in the formulated constitution. At the middle and lower levels, peacebuilding efforts succeeded in convincing South Sudanese to support the implementation of gender equality as part of conflict resolution. Keywords: Women; Peacebuilding; Gender Equality; Discrimination; South Suda